Pengaruh Polah Asuh Orang Tua Terhadap Motivasi Belajar Siswa SMA Negeri 1 Wiradesa Pekalongan - Fariqy, ghulam fariqy (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
: Ghulam Fariqy. NPM 17110099. "The Influence of Parenting Patterns on Motivation in Learning in Class XI Students of SMA Negeri 1 Wiradesa Pekalongan Regency". Thesis. Guidance and Counseling Study Program. Faculty of Education, PGRI University, Semarang. 2022. The problem in this study is that at the age of teenagers parents pay less attention to the learning development experienced by students. Parents rarely ask about the learning progress experienced by students at school because some are busy working, and others think that the student is an adult so they do not need direction and guidance from their parents anymore. The purpose of this study was to determine how the influence of parenting on motivation in learning in class XI SMA Negeri 1 Wiradesa. This type of research is quantitative research. ex-postfacto research. The population in this study were students of class XI MIPA 1 and XI MIPA 2 SMA Negeri 1 Wiradesa. The data in this study were obtained through student questionnaires. Based on the calculation of the regression test that has been carried out, it is known that the value of tcount = 3.545 with a significance value of 0.001 <0.05, then H0 is accepted, meaning that there is a significant (significant) effect of the trust variable (X) on the participation variable (Y). Based on these calculations, the hypothesis which reads "There is a positive and significant influence between parenting patterns on motivation in learning in class XI students of SMA Negeri 1 Wiradesa for the academic year 2021/2022" can be accepted as true. Based on the results of this study, the suggestion that can be conveyed is that teachers and parents must always coordinate about the activities and activities of children at school and at home in order to monitor how the results obtained by children and parents can apply appropriate parenting patterns so that between attitudes and children's learning outcomes can to be better. Keywords: Parenting, Parents, Motivation. Abstrak : Ghulam Fariqy. N